DESCRIPTIVE STUDY OF LOW BIRTH WEIGHT INFANTS AT SEPASO HEALTH CENTER - Margaritha Kamariah; Andi Lis A.G; Nino Adib (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Low birth weight (LBW) infants are a serious health issue in Indonesia. LBW is associated with high mortality rates, chronic diseases risks, and growth and developmental disorders in children. This study aims to provide an overview of LBW occurrence at Sepaso Health Center. This research employed a descriptive research design. According to Sumadi (2016), descriptive research aims to provide a description of a situation or event. A case study approach was used in this research design, where information was collected to understand a specific event or problem. The population of this study consisted of individuals with authority regarding the influence of LBW infants at Sepaso Health Center. Purposive sampling technique was utilized for sample selection. Based on the research conducted on 30 mothers with low birth weight (LBW) infants, the findings revealed that 60% of the mothers were at risk due to being below 20 years or above 35 years old, while 40% of the mothers were not at risk with ages between 20-35 years. Parity showed that 30% were nulliparous and 70% were multiparous. Maternal occupation indicated that 40% were employed and 60% were unemployed. Antenatal care (ANC) distribution showed that 40% had frequent ANC visits, while 60% had inadequate ANC visits. Maternal food consumption during pregnancy showed that 27% had good consumption, 67% had sufficient consumption, and 6% had inadequate consumption. These findings can serve as a basis for enhancing attention and care for low birth weight infants at the Sepaso Health Center. It is expected that this study can contribute to the efforts in improving the health of low birth weight infants in the region.